2003
DOI: 10.1046/j.1471-0528.2003.02105.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful myomectomy following infected ischaemic necrosis of uterine fibroids after uterine artery embolisation

Abstract: Case reportA 39 year old woman came to the gynaecology clinic with a four year history of pelvic pain and secondary infertility. She had had a miscarriage in the first trimester.One year previously she had undergone open myomectomy. Examination revealed a bulky uterus. An ultrasound scan and magnetic resonance imaging showed a fibroid on the posterior wall of the uterus measuring 9 cm in diameter.She requested uterine artery embolisation as she was keen to avoid repeat surgery and she wanted to preserve her fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…13 Leiomyomas undergo hydropic degeneration and necrosis after myolysis, 14 and ischemic necrosis after embolization. 15 Walker et al 16 reported that 58% of the women who had undergone embolization presented with increased vaginal discharge after the procedure; of these women, the discharge lasted for less than 4 weeks in 28%, 4-8 weeks in 20%, and more than 8 weeks in 16%. These researchers also reported that the persistent discharge in these patients was caused by a superficial cavity within the infarcted leiomyoma communicating with the endometrial cavity.…”
Section: Discussionmentioning
confidence: 99%
“…13 Leiomyomas undergo hydropic degeneration and necrosis after myolysis, 14 and ischemic necrosis after embolization. 15 Walker et al 16 reported that 58% of the women who had undergone embolization presented with increased vaginal discharge after the procedure; of these women, the discharge lasted for less than 4 weeks in 28%, 4-8 weeks in 20%, and more than 8 weeks in 16%. These researchers also reported that the persistent discharge in these patients was caused by a superficial cavity within the infarcted leiomyoma communicating with the endometrial cavity.…”
Section: Discussionmentioning
confidence: 99%